On the Relationship between Foreign Trade and Regional Disparity in China in the Post-Reform Era - Zhang, Qin; Jiang, Yanqing (Journal of Asian Business Strategy, 2016)
Since the reform and opening policy carried out in the 1980s, and after China joined the WTO, foreign trade becomes an important part of China’s national income. Some regions have gained great benefits from foreign trade and developed in a dramatic speed while many other regions have not caught up with the high speed of development. The present work investigates whether (and how) the development of foreign trade in China is related to the ever-increasing economic disparity across different regions. After discussing the evolutions of regional economic disparity and regional foreign trade in China, this paper, by using a linear regression method, attempts to investigate the relationship between regional foreign trade disparity and regional income disparity. Our regression results show that there exists a positive relationship between the two.